Factors that Impact The Decision to Visit Punceling Tour Ciwidey - Syahril, Dian Saeful; Yuliawati, Yupi (Fakultas Ekonomi Universitas Garut, 2024)
The objective of this research is to ascertain and elucidate the impact of tourist attractions, destination image, and facilities on the decision to visit Punceling Ciwidey. A total of 87,931 visitors to Punceling tourism in 2022 comprised the population of this study; 400 respondents comprised the sample. Verification and descriptive analysis constitute the research methodology. The data were gathered through the distribution of pre-designed questionnaires to respondents whose performance had been evaluated for validity and reliability beforehand. The findings of the conducted analysis indicate that visitor attraction, destination image, and facilities jointly and partially influence visiting decisions in a positive and significant way.